2005
DOI: 10.1007/s10557-005-1376-0
|View full text |Cite
|
Sign up to set email alerts
|

Captopril Administered at Night Restores the Diurnal Blood Pessure Rhythm in Adequately Controlled, Nondipping Hypertensives

Abstract: The aim of our study was to evaluate whether captopril administered at night, can shift the circadian blood pressure (BP) from a nondipper to a dipper pattern in adequately controlled hypertensive patients, who continued their antihypertensive therapy. In a prospective, randomized, double blind, placebo-controlled designed study, we enrolled 121 treated, adequately controlled nondipping hypertensive patients. All patients were randomly assigned to 12.5 mg captopril or placebo treatment administered at night. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…There is evidence to suggest that nighttime dosing (49)(50)(51) and diuretic therapy (52) may alter the nighttime BP pattern. However, researchers of population-based studies examining the prognostic implications of ambulatory BP have found that a less than 10% decline in nighttime BP is associated with an increased risk of all-cause mortality (15) and cardiovascular mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that nighttime dosing (49)(50)(51) and diuretic therapy (52) may alter the nighttime BP pattern. However, researchers of population-based studies examining the prognostic implications of ambulatory BP have found that a less than 10% decline in nighttime BP is associated with an increased risk of all-cause mortality (15) and cardiovascular mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…131 Nocturnal dosing of antihypertensive agents has also been associated with conversion from attenuated dipper or riser to dipper status in both controlled and refractory hypertensive patient populations. 130,[132][133][134][135] Uncontrolled short-term studies have revealed reductions in night-time BP readings along with transition from non-dipper to dipper status among normotensive and hypertensive subjects following nocturnal application of therapeutic continuous positive airway pressure (CPAP), [136][137][138] which has been associated with sympathoinhibition unlike nocturnal application of subtherapeutic CPAP or oxygen. 139 In patients with end-stage renal disease, renal transplantation has been associated with a significant lowering of the prevalence of non-dipping from 73% within the first year after transplantation to 27% following the first year after transplantation, independent of 24-hour BP and concomitant medication changes, 140 with the nocturnal BP fall correlating with renal allograft function.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…The finding that the ACEI restored the normal dipping circadian BP rhythm in 70% of the patients. Which can be explained by bedtime captopril administration significantly reduced nighttime BP and restored the normal dipping status [10].…”
Section: Discussionmentioning
confidence: 94%